Neuroprotection by Cocktails of Dietary Antioxidants under Conditions of Nerve Growth Factor Deprivation. (8th July 2015) - Amara, Flavio; Berbenni, Miluscia; Fragni, Martina; Leoni, Giampaolo; Viggiani, Sandra; Ippolito, Vita Maria; Larocca, Marilena; Rossano, Rocco; Alberghina, Lilia; Riccio, Paolo; Colangelo, Anna Maria
Abstract : Dietary antioxidants may be useful in counteracting the chronic inflammatory status in neurodegenerative diseases by reducing oxidative stress due to accumulation of reactive oxygen species (ROS). In this study, we newly described the efficacy of a number of dietary antioxidants (polyphenols, carotenoids, thiolic compounds, and oligoelements) on viability of neuronal PC12 cells following Nerve Growth Factor (NGF) deprivation, a model of age-related decrease of neurotrophic support that triggers neuronal loss. Neuroprotection by antioxidants during NGF deprivation for 24 h was largely dependent on their concentrations: all dietary antioxidants were able to efficiently support cell viability by reducing ROS levels and restoring mitochondrial function, while preserving the neuronal morphology. Moreover, ROS reduction and neuroprotection during NGF withdrawal were also achieved with defined cocktails of 3–6 different antioxidants at concentrations 5–60 times lower than those used in single treatments, suggesting that their antioxidant activity was preserved also at very low concentrations. Overall, these data indicate the beneficial effects of antioxidants against oxidative stress induced by decreased NGF availability and suggest that defined cocktails of dietary factors at low concentrations might be a suitable strategy to reduce oxidative damage in neurodegenerative diseases, while limiting possible side effects.